Residual stresses caused by static and dynamic contact interaction of composite plate and steel spherical indenter - Sviatoslav Eleonsky; Vladimir Pisarev (Fracture and Structural Integrity)
A new approach has been developed and implemented to determine the main components of residual stresses that arise as a result of the contact interaction of a spherical indenter and a flat surface of composite plate made. The experimental technique includes drilling a probe hole and measuring the increments of the diameters of this hole in the direction of the principal residual deformations by speckle interferometry. The high-quality interference fringe patterns essential for the implementation of this procedure are visualized both inside and outside the contact dimple. Data from interference measurements of in-plane displacement components are used to determine the principal components of residual stresses based on the unequivocally solution to the properly posed inverse problem. This procedure provides minimal possible errors inherent in a determination of residual stress components by measurements of local deformation response to small hole drilling in orthotropic plate. The presented studies were carried out both for static and dynamic application of contact indentation of a spherical indenter into a flat surface of samples made of laminated carbon fiber material with cross-ply stacking sequence. It is shown that the values of residual stresses, unlike indirect parameters, are a parameter that can be used to establish a correlation between the results of residual strength tests and the quantitative characteristics of the residual stress field in the vicinity of the contact dimple